Post-eruption economic recovery: Strengthening livelihoods in Lumajang Indonesia after Mount Semeru disaster - Hariyono, Hariyono; Purwono, Rudi; Sukartini, Ni Made; Madyawati, Sri Pantja; Chrisnahutama, Adrian (Privietlab, 2025)
Natural disasters in Indonesia result in significant material and nonmaterial losses. According to the National Disaster Management Agency (BNPB), disasters in 2021 have caused 709 deaths, 73 missing persons, and displaced 583,840 people. Post-disaster recovery efforts, including economic assistance, are essential for restoring people’s livelihoods. The implementation of economic assistance after the Mount Semeru eruption in the Lumajang Regency included several stages: preparation, socialization and location survey, group formation, technical guidance, provision of stimulant assistance, exit strategy planning, and monitoring and evaluation. As a result, two livestock groups were established in the Bumi Semeru Damai permanent housing area, each consisting of 10 members and legally recognized by a village decree. These groups successfully carried out daily livestock management, enhanced productivity and welfare, improved market access, and increased the understanding of livestock product marketing. The initiative fostered sustainability and independence, with the groups evolving into leading livestock centers specializing in goats in the Lumajang Regency. Critical factors supporting sustainability included a sufficient supply of animal feed that met nutritional requirements. This economic assistance program played a vital role in revitalizing the local economy by utilizing local commodities, forming community-based economic institutions, and strengthening local capacities through a disaster risk reduction approach. In addition, the program secured local government and stakeholder support, contributing to long-term recovery and alignment with sustainable regional development. This case highlights the importance of integrated economic recovery programs in post-disaster contexts for building resilience and improving community welfare.